The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/jpepsy/jsz091
|View full text |Cite
|
Sign up to set email alerts
|

Examining Differences in Parent Knowledge About Pediatric Food Allergies

Abstract: Objective Pediatric food allergy (FA) is a serious health condition that has become increasingly prevalent. Parents often play a primary role in assessing and managing risk for their child’s FAs, making it critical that they remain informed of the most recent guidelines for FA management. This study aimed to examine if diagnostic source (i.e., pediatrician vs. allergist) and child- and parent-level variables predicted parental FA knowledge using a comprehensive measure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…The study also provides an insight into the relatively low level of knowledge parents have regarding food allergy, with the average score being 39%. Similar poor levels of knowledge were reported by Luke et al 6 Children with two or more first‐degree relatives with allergic disease are at higher risk of developing food allergy while having one first‐degree relative with allergic disease moderately increases the infant's risk 7 . In our study, approximately half the parents whose infant is at an increased risk of developing a food allergy, either with one or two allergic relatives, failed to recognize this risk.…”
Section: Food Before 6 Months N (%) 6‐12 Months N (%) After 12 Months...supporting
confidence: 85%
“…The study also provides an insight into the relatively low level of knowledge parents have regarding food allergy, with the average score being 39%. Similar poor levels of knowledge were reported by Luke et al 6 Children with two or more first‐degree relatives with allergic disease are at higher risk of developing food allergy while having one first‐degree relative with allergic disease moderately increases the infant's risk 7 . In our study, approximately half the parents whose infant is at an increased risk of developing a food allergy, either with one or two allergic relatives, failed to recognize this risk.…”
Section: Food Before 6 Months N (%) 6‐12 Months N (%) After 12 Months...supporting
confidence: 85%
“…A recent study surveying parents/caregivers of children with FA found that while caregiver knowledge about pediatric food allergies is generally suboptimal, misperceptions were more frequently reported among racial/ethnic minority respondents and those reporting lower household income. 7 White children with peanut allergy in our study were more often introduced to peanut products at recommended ages compared to Black children with peanut allergy born between 2017-2019 during which time PPA Guideline implementation occurred. Our study reports similar findings to a study conducted among a predominantly White population describing challenges with parent/caregiver adherence to the PPA Guidelines and delayed peanut product introduction ( >11 months of age).…”
Section: Introductionmentioning
confidence: 70%
“…Studies in Iran [25] and Germany [13] have reported suboptimal levels of food allergy awareness among the study samples, while in contrast, some studies in Turkey [14,26] reported a moderate level of food allergy awareness. In a study examining differences in parent knowledge about pediatric food allergies [27], suboptimal FA knowledge among parents was reported. This may be due to the fact that parents can forget the information supplied by doctors, which leads to a lack of information application.…”
Section: Discussionmentioning
confidence: 99%